Introducing 'The Diverse Nature of Defence Healthcare' university module for DMS personnel. Issue Volume 161:Issue (2015)Supplement 1 (30th November 2015) - Carter, Chris; Blake, L
Abstract : Over the past 10 years the UK Defence Medical Services has deployed healthcare personnel to a variety of operational areas in support of UK Operations. The unique nature of every operational deployment, in conjunction with the wide variety of roles which healthcare staff undertake, necessitates bespoke educational preparation of the military healthcare force. This paper explores the creation and development of one of the four modules which comprise the BSc (Hons) in Defence Health Care studies, entitled 'The Diverse Nature of Defence Healthcare'. It demonstrates the unique contribution that the Defence School of Healthcare Education makes towards Generation and Preparation of the Force for deployment.